PATIENT DOSES IN COMMON DIAGNOSTIC X-RAY EXAMINATIONS - Metaxas, Vasileios I; Messaris, Gerasimos A; Lekatou, Aristea N; Petsas, Theodore G; Panayiotakis, George S (Radiation protection dosimetry, 2019)
A local survey was conducted, to evaluate the radiation dose to adult patients who underwent diagnostic X-ray examinations. Patient-related and technical data were recorded, in 1504 patients, for each of the 11 individual projections, of the 7 most common examinations performed in an X-ray room, with 1 digital radiography system. The patient entrance surface air kerma (ESAK) and the effective dose (ED) were calculated based on the X-ray tube output and the exposure parameters, as well as utilisation of suitable conversion coefficients, respectively. The 75th percentiles of the distribution of the ESAK and kerma area product (KAP) values were also established. The mean, median and 75th percentiles were compared with the national reference levels and the most common values reported at the European level through the DOSE DATAMED II project. The corresponding ED values were also compared with the average values reported for all European countries. The mean ESAK, KAP and ED values along with the uncertainty U values for chest PA, chest LAT, cranium AP, cranium LAT, cervical spine AP, cervical spine LAT, lumbar spine AP, lumbar spine LAT, pelvis AP, abdomen AP, kidneys and urinary bladder (KUB) AP were 0.12 (0.001) mGy, 0.66 (0.023) mGy, 1.01 (0.034) mGy, 0.69 (0.098) mGy, 0.72 (0.014) mGy, 0.63 (0.011) mGy, 4.12 (0.050) mGy, 5.74 (0.082) mGy, 2.57 (0.024) mGy, 1.94 (0.017) mGy, 2.47 (0.073) mGy, and 0.09 (0.001) Gy cm2, 0.38 (0.012) Gy cm2, 0.32 (0.009) Gy cm2, 0.27 (0.052) Gy cm2, 0.17 (0.004) Gy cm2, 0.21 (0.006) Gy cm2, 1.18 (0.018) Gy cm2, 1.86 (0.023) Gy cm2, 1.41 (0.012) Gy cm2, 1.27 (0.010) Gy cm2, 1.28 (0.038) Gy cm2, as well as 0.01 (0.0001) mSv, 0.05 (0.0016) mSv, 0.02 (0.0006) mSv, 0.01 (0.0012) mSv, 0.03 (0.0008) mSv, 0.03 (0.0006) mSv, 0.26 (0.0038) mSv, 0.17 (0.0022) mSv, 0.20 (0.0016) mSv, 0.23 (0.0018) mSv, 0.23 (0.0068) mSv, respectively. The 75th percentiles along with the uncertainty U values for chest PA, chest LAT, cranium AP, cranium LAT, cervical spine AP, cervical spine LAT, lumbar spine AP, lumbar spine LAT, pelvis AP, abdomen AP, kidneys and urinary bladder (KUB) AP were 0.14 (0.006) mGy, 0.88 (0.031) mGy, 1.22 (0.049) mGy, 0.94 (0.098) mGy, 0.93 (0.027) mGy, 0.78 (0.013) mGy, 5.16 (0.073) mGy, 7.24 (0.134) mGy, 2.96 (0.047) mGy, 2.59 (0.036) mGy, 3.07 (0.116) mGy, as well as 0.10 (0.0006) Gy cm2, 0.51 (0.017) Gy cm2, 0.37 (0.020) Gy cm2, 0.33 (0.040) Gy cm2, 0.23 (0.007) Gy cm2, 0.26 (0.011) Gy cm2, 1.50 (0.036) Gy cm2, 2.26 (0.035) Gy cm2, 1.61 (0.023) Gy cm2, 1.67 (0.017) Gy cm2, 1.56 (0.069) Gy cm2, in terms of ESAK and KAP values, respectively. The results were significantly lower compared with the national reference levels, the most common DRL values reported at the European level and other previously reported dose values. Patient dose surveys could contribute towards optimising radiation protection for patients, therefore, highlighting the necessity to increase the awareness and knowledge of the radiation dose in conjunction with the required image quality.